Vessel Monitoring Application Using Automatic Identification System Data - Putra, Willy Permana; Sumarudin, A.; Suheryadi, Adi; Hidayat, Risanuri (2022)
The increasing number of accidents in Indonesian waters, particularly involving traditional fishermen, has reduced the quality of Indonesian fishermen. It is due to the fact that many fishermen still do not use the Automatic Identification System on their ships, putting them at risk of causing ship collisions. Apart from the previously mentioned fact, Indonesia as a maritime country does not yet have a qualified Vessel Management System, leading to the rampant illegal activities in Indonesian waters. The quality of fishermen has decreased due to the lack of monitoring. A Vessel Management System that can monitor ships and implement an automatic identification system on fishing boats is required to mitigate these issues. The authors created this system using Laravel and Vuejs in the application development. An Agile development methodology was also used in this application creation for its fast development and flexibility in the process, allowing the system to be created quickly. © 2022 IEEE.